Per Capita Consumption and Distribution Pattern of Antibiotic in Khuzestan Province From 2016 to 2017 - Rezvan Hallaj; Behzad Sharif Makhmalzadeh; Leila Kouti; Janet Soleymani; Hossein Barzegar Bafrooei; Farideh Younesi; Kaveh Eslami (Tehran University of Medical Sciences, 2018)
Background: The overuse and misuse of antibiotics contribute to the development of antibiotic resistance, increase the incidence of adverse drug reactions, and impose high costs on the healthcare system. In Iran, the Food and Drug Administration is responsible for the surveillance of drug consumption. The aim of the present study is to assess the distribution pattern of 10 most commonly used antibiotics from drug distribution companies to private and national health pharmacies supervised by the Food and Drug Deputy of Ahvaz Jundishapur University of Medical Sciences in 2016. The administration rate of these antibiotics was also assessed by a survey of prescriptions documented by the Social Security Organization and Health Insurance. Methods: The distribution pattern of 10 antibiotics was obtained from pharmaceutical distribution companies. The per capita consumption of antibiotics with and without prescription was determined by the Social Security Organization and Health Insurance. Results: More than half of the total distributions of all antibiotics in the cities of Khuzestan Province were related to private pharmacies. Many surveyed cities had a high percent of antibiotic consumption without prescription. Conclusion: The accurate recording of the distribution of antibiotics by pharmaceutical companies and the submission of monthly and annual reports to food and drug deputies are necessary. It is also necessary to increase the surveillance of pharmacies and the process of antibiotic provision.